Penyuluhan Hukum Peraturan Daerah Khusus Provinsi Papua Nomor 23 Tahun 2008 Tentang Hak Ulayat Masyarakat Hukum Adat Dan Hak Perorangan Warga Masyarakat Hukum Adat Atas Tanah Di Kampung Asei Besar Distrik Sentani Timur Kabupaten Jayapura - Sella Petrix Pelupessy; Berd Elkiopas Pelupessy; Y. D. W. Susi Irianti; Eddy Pelupessy; Marthinus Solossa; Nur Asmarani; James Yoseph Palenewen; Lena Claudia Angwarmasse; Evi Selviani; Vivilia Agnata Mudi; Dwight Nusawakan; Firman (AMMA : Jurnal Pengabdian Masyarakat, 2025)
This community service was carried out with the title of Legal Counseling on the Special Regional Regulation of Papua Province Number 23 of 2008 Concerning the Customary Rights of Customary Law Communities and the Individual Rights of Customary Law Community Members to Land in Asei Besar Village, East Sentani District, Jayapura Regency, this activity was carried out for partners due to cases from partners regarding their lack of understanding regarding the resolution of customary land disputes based on applicable laws and regulations in order to obtain legal certainty and where the disputing parties do not want to give in or want to win alone so that with the expertise possessed by the servants, they can carry out legal counseling so that the disputing parties both win or achieve a win-win solution. The method of implementing this community service is carried out through lectures and discussions held on Saturday, August 30, 2025, which was held in Asei Besar Village, East Sentani District, Jayapura Regency by providing knowledge to partners regarding land dispute resolution in general there are two types, namely dispute resolution through Litigation and Non-Litigation to obtain legal certainty, this activity begins with preparation and coordination, then presentation of material on how to resolve customary land disputes based on applicable laws and regulations. The output of this community service is to provide an understanding to partners about how to resolve disputes through Non-Litigation channels along with the advantages and disadvantages of resolving these disputes and also provide legal assistance to partners to resolve cases related to customary land disputes.